ASSESSMENT OF SCORES IN DECISION MAKING IN METASTASES OF THE SPINE - Ferreira,Marcus Vinicius de Oliveira (2015)
Objective : The aim of this study is to assess the intra- and interobserver concordance of SINS, Harrington, Tokuhashi and Tomita scores among general orthopedic surgeons and spine surgeons with experience above 5 and 10 years in the evaluation of patients with spinal metastasis. Methods : Twenty cases of patients with metastatic lesion of the spine were presented to 10 examiners and the scores aforementioned have been applied. After six weeks, the cases were reintroduced in a different order and data were analyzed. Results : The intraobserver reliability showed better agreement in SINS score among examiners with less experience and Harrington and Tomita scores among those who had more than 10-year experience. The interobserver reliability of the examiners of the group with over 10-year experience showed higher precision when using these scores, especially Harrington and Tomita. The SINS score was the choice for daily practice and was able to modify the management more often. Conclusions : This study demonstrated that the use of predictive scores of instability, Harrington, and prognosis, Tomita, had a higher intra- and interobserver reliability particularly among spine surgeons with experience above 10 years.